2021
DOI: 10.1038/s41598-021-94732-1
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of gene expression changes in a high replicate and open-source dataset of differentiating hiPSC-derived cardiomyocytes

Abstract: We performed a comprehensive analysis of the transcriptional changes occurring during human induced pluripotent stem cell (hiPSC) differentiation to cardiomyocytes. Using single cell RNA-seq, we sequenced > 20,000 single cells from 55 independent samples representing two differentiation protocols and multiple hiPSC lines. Samples included experimental replicates ranging from undifferentiated hiPSCs to mixed populations of cells at D90 post-differentiation. Differentiated cell populations clustered by time p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 96 publications
(156 reference statements)
3
30
0
Order By: Relevance
“…Because hiPSC-CMs are relatively immature when cultured in 2D without exogenous stimulation, they uniquely facilitate the understanding of early-stage, direct consequences of HCM mutation(s) without other secondary changes in animal models or patients. Based on single-cell 2D cardiac differentiation showing that MYH6 is abundant at day 12 and subsequently MYH7 predominates ( Grancharova et al, 2021 ), we assessed an early time point (Day 15) and a later time point (Day 45) to facilitate the early-stage understanding of the functional contributions of MYH6 as well as MYH7 converter domain mutations. Additionally, generation of hiPSCs with multiple HCM mutations including variants of unknown significance or sarcomere gene negative HCM, may allow understanding of early stage molecular and physiologic changes that have been challenging to assess in animal models or patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because hiPSC-CMs are relatively immature when cultured in 2D without exogenous stimulation, they uniquely facilitate the understanding of early-stage, direct consequences of HCM mutation(s) without other secondary changes in animal models or patients. Based on single-cell 2D cardiac differentiation showing that MYH6 is abundant at day 12 and subsequently MYH7 predominates ( Grancharova et al, 2021 ), we assessed an early time point (Day 15) and a later time point (Day 45) to facilitate the early-stage understanding of the functional contributions of MYH6 as well as MYH7 converter domain mutations. Additionally, generation of hiPSCs with multiple HCM mutations including variants of unknown significance or sarcomere gene negative HCM, may allow understanding of early stage molecular and physiologic changes that have been challenging to assess in animal models or patients.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that WTC and its derived transgenic lines have been broadly used in the cardiac stem cell field, we have investigated MYL2 expression in WTC-derived CMs from multiple labs based on their scRNA-seq results. We found that while MYL2 was barely detected in the WTC-derived CMs before differentiation day 30 in several studies, it was expressed in other hiPSC line-derived CMs with the same differentiation conditions [ 52 , 53 , 54 ]. However, there are some exceptions where MYL2 was found to be expressed in the WTC-derived CMs on day 30 in one study and day 90 in another.…”
Section: Heart Structure Developmentmentioning
confidence: 86%
“…However, there are some exceptions where MYL2 was found to be expressed in the WTC-derived CMs on day 30 in one study and day 90 in another. Both studies generated the CMs using a monolayer with small molecules protocol [ 53 , 55 ] ( Table 1 ). The cause of the differences in gene expression across the studies is still a mystery to us, but it will be important to investigate whether this expression variation also exists in other genes and other cell lines.…”
Section: Heart Structure Developmentmentioning
confidence: 99%
“…As for human vascular cells, Su et al (2018) used scRNA-seq to study the dynamic lineage of coronary arteries and found that COUP-TF2 blocked arterial formation in the pre-arterial stage. Grancharova et al (2021) used scRNA-seq to profile gene expression during the differentiation of human-induced pluripotent stem cells (hiPSCs) to cardiomyocytes, revealing genetic features which could identify stages of differentiation or maturation in differentiating cardiomyocytes. Currently, scRNA-seq has become an important tool for studying embryological development of the cardiovascular system.…”
Section: Scrna-seq and Cardiovascular Developmentmentioning
confidence: 99%
“…In contrast, single-cell RNA sequencing (scRNA-seq) is used to detect the mRNA level of individual cells (Paik et al, 2020). In the field of modern cardiovascular research, it is a powerful tool for elucidating cellular heterogeneity, cell types, intercellular crosstalk, and trajectory analysis of cellular dynamics (Litviňuková et al, 2020;Cheng et al, 2021;Grancharova et al, 2021;Kan et al, 2021). In this review, we summarize published research using scRNA-seq on the embryological development of the cardiovascular system and pathogenesis of CVD.…”
Section: Introductionmentioning
confidence: 99%